Tourist arrivals to Malaysia from Muslim countries - Mat Ghani, Gairuzazmi (Elsevier, 2016)
The Malaysian government has introduced many Muslim-friendly tourism initiatives to attract Muslim tourists. However, the number of tourist arrivals to Malaysia from Muslim countries is smaller than the number of arrivals from non-Muslim countries, which calls into question the effectiveness of Muslim-friendly tourism initiatives. This study used the bilateral tourism flows gravity model to estimate the effect of Muslim country on the number of tourist arrivals. The results show that the Muslim country effect is positive,where it increases arrivals by about 90% relative to non-Muslim countries. The low number of arrivals from Muslim countries is due to the low per capita income of many Muslim countries; furthermore, the populations of Muslim countries with high per capita income are typically small. The geographical distance of Muslim countries from Malaysia is also a factor that constrains the number of arrival.